Accuracy of Estimated Fetal Weight by Clinical Assessment and Ultrasonography (Medical Forum Monthly, 2024)
Objective: To compare accuracy of estimating fetal weight of term fetus by clinical assessment and Ultrasonography.Study Design: Comparative Clinical Trial Study.Place and Duration of Study: This study was conducted in obstetrics and gynecology unit of Hayat Abad Medical Complex. Materials and Methods: - This study was carried out on 300 subjects, with full term; normal pregnancy. Patients had fetal weight estimation by two approachesClinical assessment done by Leopold’s maneuvers and symphysio fundal height in centi-meters andSonographic measurement by using Toshiba capacee with curvilinear transducer of 3.5 MHz.Birth weight at delivery was used on gold standard.The accuracy of these two methods of estimating fetal weight was compared using student t test, and ϰ2 P> .05 was considered significant.Result: Out of 300 cases, 292 cases were compared both. Ultrasonically and by clinical assessment .while 8 babies could not be picked up of ultrasonically because of fetal weight more than 4.0 KG , out of 292 cases (218) 72.7% were assessed. Correctly by clinical assessment while (224) 74.7% were assessed .correctly by ultrasonography.Conclusion: - Clinical assessment is equally accurate as ultrasonography in normal term birth weight estimation.